2022
DOI: 10.1093/jleo/ewac002
|View full text |Cite
|
Sign up to set email alerts
|

Fighting Organized Crime by Targeting their Revenue: Screening, Mafias, and Public Funds

Abstract: Repressive policies to fight criminal organizations are often met with a violent response from criminal groups. Are non-repressive strategies more effective? Targeting criminal revenues can be a powerful tool if the threat of investigation is credible and if criminals are unable to displace their activity to avoid controls. We study an Italian policy designed to tackle mafia misappropriation of public funds by screening companies applying for subsidies over 150,000 Euros. Using all subsidies to firms co-financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…Our results thus complement and extend other recent work that documents the e↵ectiveness of city council dissolution in favoring better long-run local economic performance (Fenizia and Saggio, 2022), fostering women's political empowerment (Baraldi and Ronza, 2022), enhancing the quality of elected politicians (Daniele and Geys, 2015), and improving tax collection and the allocation of public funds (Di Cataldo and Mastrorocco, 2021). Moreover, since some studies have shown that repressive policies bring about a violent reprisal from criminal organizations (e.g., Calderón et al, 2015;Castillo and Kronick, 2020), our analysis contributes to the literature studying the e↵ectiveness of non-repressive government measures in fighting organized crime activities (Daniele and Dipoppa, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…Our results thus complement and extend other recent work that documents the e↵ectiveness of city council dissolution in favoring better long-run local economic performance (Fenizia and Saggio, 2022), fostering women's political empowerment (Baraldi and Ronza, 2022), enhancing the quality of elected politicians (Daniele and Geys, 2015), and improving tax collection and the allocation of public funds (Di Cataldo and Mastrorocco, 2021). Moreover, since some studies have shown that repressive policies bring about a violent reprisal from criminal organizations (e.g., Calderón et al, 2015;Castillo and Kronick, 2020), our analysis contributes to the literature studying the e↵ectiveness of non-repressive government measures in fighting organized crime activities (Daniele and Dipoppa, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…Our results thus complement and extend other recent work that documents the e↵ectiveness of city council dissolution in favoring better local economic performance (Fenizia and Saggio, 2022), fostering women's political empowerment (Baraldi and Ronza, 2022), enhancing the quality of elected politicians (Daniele and Geys, 2015), and improving tax collection and the allocation of public funds (Di Cataldo and Mastrorocco, 2022). Moreover, since some studies have shown that repressive policies trigger violent reprisals from criminal organizations (e.g., Calderón et al, 2015;Castillo and Kronick, 2020), our analysis contributes to the literature studying the e↵ectiveness of non-repressive government measures in fighting organised crime activities (Daniele and Dipoppa, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…Recent Italian measures against mafia infiltration on politics have aimed at combating bribery. These measures can be defined as non-repressive in that they are directed to cutting o↵ the economic resources of organised crime, not engaging in an explicit battle against local clans through stepped-up deployment of law enforcement bodies (Daniele and Dipoppa, 2022). Nonetheless, non-repressive measures can reduce the expected overall payo↵ to organised crime from influencing political decisions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the empirical front, Le Moglie and Sorrenti (2022) compare provinces with high versus low presence of OCGs before and after the 2008 financial cri-sis and find that provinces with less presence of OCGs have been subject to a lower drop in the number of new firms, suggesting that OCGs helped firms overcome the reduction in the availability of credit. Daniele and Dipoppa (2022) documents the strategic behavior of firms participating in public procurement projects to elude screenings to detect mafia-connected firms. Calamunci and Drago (2020) find that the assignment of infiltrated firms to judicial investigations has a positive spillover on competing firms suggesting a large burden imposed by infiltrated firms on other firms.…”
Section: Related Literaturementioning
confidence: 99%

Mafias and Firms

Arellano-Bover,
De Simoni,
Guiso
et al. 2024
Preprint